1967
DOI: 10.1161/01.res.21.5.641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decreasing the Force of Right Atrial Contraction on Right Ventricular Stroke Volume

Abstract: The effect of reducing the force of right atrial contraction on right ventricular stroke volume was determined in anesthetized open-chest dogs. Atrial contractile force, measured directly with a strain-gauge arch, was decreased by electrical stimulation of the right vagus nerve; right ventricular stroke volume was measured with an electro-magnetic flowmeter. Heart rate was maintained constant by electrical stimulation of the right atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…From our study, we think that we could explain the indirect mechanical relationships between the right ventricular function and the right atrial dynamic contraction. From the physiological point of view, the contractile function of the atria has a strong relation to the thrombogenesis or thrombosis (Williams, et al, 1967;Wolf, et al, 1991;Lim, et al, 2013). Our focus and the data from this study suggested that the dynamics is one of the other factors to promote total flow dynamics in the pulmonary circulation as well as systemic circulation with the capability of elimination of stroke events.…”
Section: Discussionmentioning
confidence: 62%
“…From our study, we think that we could explain the indirect mechanical relationships between the right ventricular function and the right atrial dynamic contraction. From the physiological point of view, the contractile function of the atria has a strong relation to the thrombogenesis or thrombosis (Williams, et al, 1967;Wolf, et al, 1991;Lim, et al, 2013). Our focus and the data from this study suggested that the dynamics is one of the other factors to promote total flow dynamics in the pulmonary circulation as well as systemic circulation with the capability of elimination of stroke events.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, the RA pressure tracing in all TI dogs were characteristic of tricuspid insufficiency. Mean right ventricular pressure in TI dogs (mean systolic = 43 ± 1.2 mm Hg, n = 7) was slightly higher than in open-chest, chlorolose-anesthetized dogs (RV systolic pressure = 20 mm; range 16-42 mm Hg) as reported by Boyd and Williams (1967).…”
Section: Right Atrial Pressurementioning
confidence: 53%